2015
DOI: 10.1111/ases.12191
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy‐assisted transduodenal excision of superficial non‐ampullary duodenal epithelial tumors

Abstract: LATDE could eliminate the possibility of peritoneal or port-site seeding of tumor cells because the duodenotomy and tumor excision are performed extracorporeally. The meticulously hand-sewn closures of the mucosal defect and duodenotomy can minimize the possibility of postoperative hemorrhage and/or anastomotic leakage. LATDE is a feasible, safe, and minimally invasive treatment for patients with superficial non-ampullary duodenal epithelial tumors that have no risk of lymph node metastasis in the first and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Other authors have also successfully used laparoscopic primary closure to close the duodenal defect after resection of duodenal tumours without major complications. [ 8 14 22 ] These studies show that laparoscopic primary closure is a feasible and safe option for the closure of duodenal defects.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other authors have also successfully used laparoscopic primary closure to close the duodenal defect after resection of duodenal tumours without major complications. [ 8 14 22 ] These studies show that laparoscopic primary closure is a feasible and safe option for the closure of duodenal defects.…”
Section: Discussionmentioning
confidence: 96%
“…The LECS technique reported by Sakon et al .,[ 8 ] endoscopy-assisted laparoscopic full thickness resection reported by Ohata et al .,[ 13 ] and laparoscopy-assisted transduodenal excision technique reported by Abe et al . [ 14 ] are technically more suitable for the resection of non-ampullary duodenal lesions. Closure of the residual defect in the case of large tumours is, however, still challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Totally laparoscopic local full‐thickness resection without a linear stapler (i.e. laparoscopic resection by opening the duodenum under aeroperitoneum and closure by intracorporeal sutures) and laparoscopic‐endoscopic cooperative surgery may pose a significant risk of peritoneal seeding of tumor cells . Tumor cells may spill into the peritoneal cavity during these procedures, leading to tumor cell seeding .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, resection of a tumor near the ampulla of Vater under direct vision is a reasonable approach. Abe et al reported laparoscopy-assisted transduodenal excision of superficial non-ampullary duodenal epithelial tumors [12]. They excised tumors through a 4-cm mini-laparotomy after mobilizing the duodenum laparoscopically.…”
Section: Discussionmentioning
confidence: 99%